Do chorionic villus samplings (CVS) or amniocenteses (AC) induce RhD immunisation? An evaluation of a large Danish cohort with no routine administration of anti‐D after invasive prenatal testing. (25th July 2019) - Kristensen, SS; Nørgaard, LN; Tabor, A; Sundberg, K; Dziegiel, MH; Hedegaard, M; Ekelund, CK
Abstract : Objective: To evaluate the risk of inducing RhD immunisation in pregnancies of RhD‐negative mothers with an RhD‐positive fetus undergoing chorionic villus samplings (CVS) or amniocenteses (AC). Design, setting and population: Registry‐based study in a Danish cohort which has not been given rhesus prophylaxis. Methods: Data were retrieved from the Department of Clinical Immunology at Rigshospitalet. All RhD‐negative women carrying an RhD‐positive fetus with screen test results from weeks 8–12 and weeks 25–29 were linked to data from the Danish Fetal Medicine Database. Data were divided into cases where no invasive prenatal diagnostic procedure was performed, cases that had AC performed, and cases that had CVS performed. Main outcome measures: A comparison of the proportion of women who developed RhD immunisation between the two screen tests. Results: The cohort consisted of 10 085 women: 9353 had no invasive procedures performed, 189 had AC and 543 had CVS performed. No women were immunised spontaneously or due to the procedure between the first and second screen test in the group with no procedure performed, or in the AC group. One woman was immunised in the CVS group. When comparing the proportion of women who was immunised in the CVS group with the no invasive test group a non‐significant difference was found ( P = 0.055). Conclusion: The RhD immunisation rate before gestational weeks 25–29 in RhD‐negative women carrying an RhD‐positive fetus is very low, even in women undergoing prenatal invasive testing without rhesus prophylaxis. Tweetable abstract: The RhD immunisation rate during pregnancy is very low even in women undergoing prenatal invasive testing. Tweetable abstract: The RhD immunisation rate during pregnancy is very low even in women undergoing prenatal invasive testing.